Medulloblastoma: biology and immunotherapy - Poggi, Alessandro; Reggiani, Francesco; Azevedo, Helena S.; Raffaghello, Lizzia; Pereira, Rui Cruz (Frontiers in Immunology, 2025)
Medulloblastoma is an aggressive central nervous system tumor affecting children more commonly between the ages of 5-9. It is usually localized in the cerebellum, leading to diffusion of tumor cells through the cerebrospinal fluid and metastases to other portions of the brain and spinal cord. Conventional treatment consists of surgical resection followed by adjuvant radiation and/or chemotherapy. The side effects of these therapies are critical to consider, especially given that patients are in a distinct stage of their lives. In addition, the overall survival is not satisfactory ranging from 50-90% depending on the type of medulloblastoma. The molecular characterization has broadly subdivided medulloblastoma into four subgroups, and more recently, the single-cell transcriptomics studies have further identified several other subgroups. Important advances have been reported on the cell origin, their plasticity, heterogeneity of genetic and epigenetic alteration, and interaction with the immune and stromal components of the tumor microenvironment. Research studies on these key points are essential to make advances in planning the application of conventional therapies together with immunotherapies. Herein, we discuss the main advances recently obtained on medulloblastoma biology and immunotherapies. Overall, the biological and molecular features of medulloblastoma are briefly summarized to understand the reason for the application of the old and new immunotherapies. Immunotherapies considered include the identification of potential medulloblastoma neoantigens and tumor-associated antigens to generate antigen-specific T lymphocytes. The main antigens expressed by medulloblastoma cells and/or by components of the tumor microenvironment will be considered as the molecular targets of antibodies, antibody derivatives, and chimeric antigen receptor effector cells to improve the conventional therapies. In the last portion of this review, the brief analysis of the activating and inhibiting receptors expressed by antitumor T, natural killer, and unconventional T cells can give new insights into the potential treatment of medulloblastoma.